Physicochemical Quality Assessment and Multivariate Statistical Analysis of Groundwater Quality in Basrah, Iraq - Salman Dawood, Ammar; Sagban Khudier, Ahmed; Naeemah Bashara, Ahmed (International Journal of Engineering and Technology, 2018)
Groundwater is the very vital natural resource which must not be essentially utilized and sustained unless its quality is precisely evaluated. A total of 41 groundwater samples were collected from selected areas within Basrah province in 2014 to assess its suitability for irrigation uses. Physicochemical indices such as permeability index (PI 5.44 to 84.32 meq L-1), percentage of sodium (Na% 8.87 to 51.03 meq L-1) and sodium adsorption ratio (SAR 0.11 to 39.33 meq L-1) indicate that the groundwater in the study area is suitable for irrigation except for few locations. The results show that the high values of total dissolved solids (TDS > 3000 mg L-1) for some samples minimized their application for irrigation. Principal component and cluster analyses were usually used as a supporting tool for assistance arrange and interpret the chemical analysis. Three principal components explanation for most of the variability in the groundwater data were represented.